High frequency of primary refractory disease and low progression-free survival rate of Hodgkin's lymphoma: a decade of experience in a Latin American center - Jaime Pérez, José Carlos; Gamboa Alonso, Carmen Magdalena; Padilla Medina, José Ramón; Jiménez Castillo, Raúl Alberto; Olguín Ramírez, Leticia Alejandra; Gutiérrez Aguirre, César Homero; Cantú Rodríguez, Olga Graciela; Gómez Almaguer, David (2017)
Background: Reports dealing with clinical outcomes of classical Hodgkin’s lymphoma in lowto middle-income countries are scarce and response to therapy is poorly documented. This report describes the characteristics and clinical outcomes of patients with classical Hodgkin’s lymphoma from a single institution in Latin America. Method: A retrospective study was conducted over ten years of patients with classical Hodgkin’s lymphoma treated at a referral center. Progression-free and overall survival rates were estimated by Kaplan–Meier analysis. The univariate Cox regression model was used to estimate associations between important variables and clinical outcomes. Main results: One hundred and twenty-eight patients were analyzed. The mean age was 28.5 years. The five-year progression-free and overall survival were 37.3% and 78.9%, respectively. Of the whole group, 55 (43%) were primary refractory cases. Only 39/83 (47%) patients with advanced disease vs. 34/45 (75.6%) in early stages (p-value = 0.002) achieved complete remission. Those with advanced disease had a five-year overall survival of 68.7% vs. 91.8% for early disease (p-value = 0.132). Thirty-one patients relapsed (24.2%) and 20 (64.5%) received a transplant. The hazard ratio for progression with bone marrow infiltration was 2.628 (pvalue = 0.037). For death, an International Prognostic Score ≥4 had a hazard ratio of 3.355 (p-value = 0.050) in univariate analysis. Two-thirds of classical Hodgkin’s lymphoma patients diagnosed at advanced stages had a low progression-free survival but an overall survival similar to high-income countries.